Gender does not make the difference: interest in STEM by gender is fully mediated by technical socialization and degree program - Goreth, Sebastian; Vollmer, Christian (International journal of technology and design education, 2023)
In Germany, there is a shortage of skilled workers in the fields of science, technology, engineering, and mathematics (STEM) and especially in technology with declining interest in technology and with supposedly fewer teachers in technology education in the next 20 years. The present study examined whether students' interest in STEM is dependent on their career choices (i.e., their degree program), their technical socialization, their personality, and gender. A survey in Germany, Baden-Wuerttemberg (N = 350) examined gender-specific differences in teacher training students with and without technology and engineering students via structural equation modelling with the mediators personality, technical socialization, and degree program. Results show that interest in STEM by gender is fully mediated by technical socialization and degree program. Solutions for the reduction of the staff shortage and gender gap in the technical domain are discussed and it is suggested that an integration of technology lessons in the school curriculum and a reduction of gender normatives may help.